Dynamic Mechanical Properties of Vietnam Modified Natural Rubber via Grafting with Styrene. (27th December 2017) - Dung, T. A.; Nhan, N. T.; Thuong, N. T.; Viet, D. Q.; Tung, N. H.; Nghia, P. T.; Kawahara, S.; Thuy, T. T.
Abstract : The dynamic mechanical behavior of modified deproteinized natural rubber (DPNR) prepared by graft copolymerization with various styrene contents was investigated at a wide range of temperatures. Graft copolymerization of styrene onto DPNR was performed in latex stage using tert-butyl hydroperoxide (TBHPO) and tetraethylene pentamine (TEPA) as redox initiator. The mechanical properties were measured by tensile test and the viscoelastic properties of the resulting graft copolymers at wide range of temperature and frequency were investigated. It was found that the tensile strength depends on the grafted polystyrene; meanwhile the dynamic mechanical properties of the modification of DPNR meaningfully improved with the increasing of both homopolystyrene and grafted polystyrene compared to DPNR. The dynamic mechanical properties of graft copolymer over a large time scale were studied by constructing the master curves. The value of b T has been used to prove the energetic and entropic elasticity of the graft copolymer.